Investigating Factors affecting Staycation Intention in Indonesia Hotel using Theory of Planned Behaviour Framework - Antonius Adi; Douwes Lasmana; Princess Felicia Chandrawati (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
Abstract This research investigate and analyze the implementation of Theory of Planned Behaviour on Staycation Intention. This research was conducted using Partial Least Squares - Structural Equation Modeling Method. The Softtware used in Analyzing the Data was SMARTPLS 4. Results show that Staycation Intention were affected by Perceived Behavioural Control and Attitude but were not affected by Subjective Norm in Indonesian Hotel Context. The limitation of this study are: First, this study only analyzes from TPB to explain the intention to do staycation. Secondly, this study only analyzes from Indonesian hotel customer. Contribution: This study contributes to the existing Theory of Planned Behaviour, perceived behavioural control subjective norm, attitude and behavioural intention Literature. Practically, this research helps Marketing Manager of an Indonesian Hotel in attracting customer using customer’s staycation intention in staying at Indonesian Hotel Keywords: Theory of Planned Behaviour, attitude, subjective norm, perceived behavioural control, Behavioural Intention.